Sense of humour and adolescents’ cognitive flexibility - K.G.F. Esterhuyse; N. Nortje; A. Pienaar; R.B.I. Beukes (South African Family Practice)
Objective: There is a lack of research on humour among adolescents in South Africa. This article examines cognitive flexibility and humour. The objective was to investigate the roles of gender and language as possible moderating variables in the relationship between adolescents’ cognitive flexibility and sense of humour.